The Disguise of Cyber Crime in Illegal Investment Entities Post the Re-formulation of Law No. 11 of 2020 Concerning Job Creation in Indonesia - Edi Ribut Harwanto (Eduvest - Journal of Universal Studies, 2024)
This research delves into cybercrime in the post-truth era, where falsehoods are often masked as truths. This phenomenon, known as "talbis talbis," gives rise to illegal activities in the cyber world that exploit cybercrime scams such as phishing, pharming, sniffing, money mule, and social engineering. Despite being harmful, online fraud crimes are sometimes perceived positively by the public. Data from the Ministry of Communication and Information of the Republic of Indonesia in 2022 indicates that a majority of respondents have experienced online digital fraud, especially through fake gift schemes and illegal online loans. The Financial Illegal Activity Eradication Task Force (PASTI) has blocked illegal financial entities, including bogus investments and illegal online loans. Illegal investment crimes primarily rely on duplicating licensed entity websites, deceiving the public with promises of high returns. This study reveals the modus operandi of domestic illegal investment crimes and compares them with regulations governing foreign direct investment. The conclusion emphasizes the need for assertiveness from PASTI and the Investment Alert Task Force of the Financial Services Authority in supervising and providing legal protection for legal foreign direct investment activities in Indonesia.